Stressors and coping strategies of selected student teachers in the University of the Philippines Diliman - Ariola, Helenay Ann Cantor
Stress is an individual's reaction to a changing and demanding environment. Change happens all the time and stress is an individual's response to change. Student teachers are not exempted from stress. They feel that their teaching practicum is a very stressful experience. Thus, this study sought to determine the student teachers' stress vulnerability, identify the stressors, categorize their stress management strategies for future student teachers. There were 66 student teachers, chosen through purposive sampling, who participated in the study. A survey questionnaire was used to determine the respondents' stress vulnerability, while an in-depth interview was conducted to collect other essential data. Data were interpreted using statistical/content analysis and qualitative description. Based on the results, majority (51.22%) of the respondents were not stressed , while 19 (46.34%) were found to be susceptible to stress. Stressors identified by student teachers include completion of practicum teaching requirements, academic load, personal and social issues, extra-curricular activities, physical, and environmental factors. Student teachers were classified into four coping types: problem-focused coping. Majority (57.14%) of the student teacher's used the avoidant coping type. Among the respondents, 22 chose sharing of experiences with their co-student teachers as their way of coping stress. A list of problem-focused and positive appraisal coping strategies was generated from the study for future student teachers' use.